Impact of Postoperative Radiotherapy on Overall Survival in Patients with pN1 Non-Small Cell Lung Cancer - V. A. Solodkiy; V. M. Sotnikov; V. D. Chkhikvadze; N. V. Nudnov; S. D. Trotsenko (Вестник рентгенологии и радиологии, 2022)
Objective: to comparatively analyze overall survival (OS) in patients with non-small cell lung cancer (NSCLC) with affected lymph nodes (pN1) of the lung root after surgical and combination treatment with postoperative radiotherapy (PORT). Subjects and methods. OS was studied in 310 patients with grade 2-3 NSCLC. (pT1a-4N1M0): in 101 patients after lobectomy/bilobectomy, pulmonectomy with ipsilateral mediastinal lymphadenectomy and in 209 patients after combination treatment with the similar surgical volume and hypofractionated PORT (a single focal dose (SFD) of 3 Gy; 5 fractions per week, a cumulative focal dose (CFD) of 36-39 Gy (43.2-46.8 Gy-eq)) or classical fractionation (SFD2 Gy, 5 fractions per week, CFD44 Gy). An analysis was carried out in the groups of patients younger and older than 60 years with central or peripheral cancer, squamous cell carcinoma or adenocarcinoma, with different tumor grading according to the T criterion (T1-4). Results. PORT in radically operated patients with NSCLC increased 5- and 10-year OS rates only in central squamous cell lung cancer (56.1% and 39.5% vs.25.4% and 4.3%, p = 0.002). This group receiving combination therapy showed a statistically significant increasing trend in 5-year OS rates for both pT1-2 tumors (57.5% vs. 21.3%, respectively, p = 0.013) and pT3-4 tumors (53.9% versus 26.0%; p = 0.044), so did patients younger than 61 years (65.5% vs.29.4%, p = 0.008) and those over 60 years old (47.5% vs.21.3%, p = 0.047). Patients with peripheral squamous cell carcinoma or lung adenocarcinoma at any site exhibited no statistically significant increase in OS after PORT. In general, the 5- and 10-year OS rates in the compared groups were statistically significantly higher in the PORT group (47.9% and 28.9% vs. 27.1% and 11.4, p = 0.006). None of the analyzed subgroups showed a decrease in OS after PORT. Conclusion. In patients with pN1 NSCLC who had radical surgery via lobectomy/bilobectomy or pulmonectomy with ipsilateral mediastinal lymphadenectomy, PORT can be recommended only for those with central squamous cell carcinoma, regardless of tumor size and age group. In other subgroups of patients with pN1 NSCLC, PORT can only be performed within the scientific protocols. The expediency of PORT after bilateral mediastinal lymph node dissection needs to be investigated.